Negotiating Autonomy: Lived Experiences of Female Living Organ Donors in Turkey - Demirhan, Sezen (Conatus - Journal of Philosophy, 2025)
One of the most significant developments in the field of health in the past century is organ transplantation. While often regarded as a life-saving solution for patients with end-stage organ failure, the lived experiences of living organ donors – especially women – remain underexplored in the literature. This study, conducted between 2022 and 2024, employed qualitative methods and a feminist phenomenological design. The study examines how socio-cultural expectations, kinship obligations, and internalized gender norms intersect to influence women’s decision-making processes in living organ donation. Among living donors, those who donate a liver or a kidney take on significant physical and psychological risks, making their perspectives particularly important for ethical reflection. Based on interviews with 18 female donors in Turkey, the findings reveal how women's lived experiences of donation are shaped by their embodied vulnerability, relational roles, and the moral weight of familial obligation. Rather than autonomous acts made in isolation, these decisions emerge within gendered landscapes marked by asymmetrical power dynamics and cultural expectations. By attending to how women articulate their experiences of bodily sacrifice, risk, and post-donation subjectivity, this phenomenological inquiry highlights the necessity of integrating a gender-sensitive lens into bioethical discourse – one that recognizes how normative frameworks and structural inequalities shape and constrain women’s autonomy in living organ donation.